Online versus offline esports tournaments: prize structure and individual performance - Shenkman, E.; Molodchik, M.; Parshakov, P. (Journal of Sports Economics, 2025)
This article examines whether the online context affects tournament theory incentive mechanisms. It investigates the impact of prize structure on player performance in eSports under online and offline conditions. Using a quasi-experimental approach with data from the Counter-Strike Global Offensive eSports scene, the study finds that high prize distributions increase individual output in both settings, but the incentive effect is weaker in online events.